Research on the Effect of Driving Behavior Recognition on Safe Driving of Elderly Persons - ARAKAWA, Yuta; TAKAHASHI, Yukihiro; TAKADA, Kazuyuki; MIYAUCHI, Kota (Journal of the Eastern Asia Society for Transportation Studies, 2024)
Traffic accidents caused by elderly drivers is a serious social problem in Japan facing super aging society. The traffic accidents are mainly caused by decline in physical and cognitive abilities due to aging. Today, the new technologies such as automated driving is developing toward the realization of a safe automotive society. However, it will take a considerable amount of time before such new technologies are widely used in the society. Therefore, safe driving awareness remains an important means of reducing the occurrence of traffic accidents. In this study, safe driving management was conducted for elderly drivers. Driving data of the elderly drivers were collected and analyzed, and a driving evaluation sheet was created. It was verified whether drivers who received the driving evaluation sheet would practice safer driving by recognizing their own driving. As a conclusion, it became clear that driving behavior recognition by the feedback effects on safer driving.